Tindak Pidana Politik Uang di Indonesia Pada Saat Pemilu Perspektif Fiqh Jinayah dan Hukum Positif - M. Husni Mubarok (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2021)
Elections are important in a democracy that adheres to a representative system to determine a state leader, especially Indonesia, whose leadership system is presidential or also known as the congressional system. The function of elections is to act as a filter for